Effect of loading direction on the shaft resistance of jacked piles in dense sand. Issue 1 (24th April 2018) - Galvis-Castro, A. C.; Tovar-Valencia, R. D.; Salgado, R.; Prezzi, M.
Abstract : The design of piles subjected to tensile loading is usually done by applying a correction factor on the shaft resistance calculated for compressive loading, but experimental data on what this correction factor should be are limited. This paper presents the results of a series of tensile–compressive (TC) and compressive–tensile (CT) static loading tests performed on instrumented model piles (with three different values of surface roughness) jacked into dense sand samples prepared in a half-cylindrical calibration chamber with digital image correlation (DIC) capability. Digital images of the model pile and sand were taken during loading of the pile in each test and processed using the DIC technique to obtain the soil displacement and strain fields. Results from local sensors showed that the ratio of the tensile-to-compressive shaft resistance of jacked piles is always less than one and depends on both the sequence of loading (CT or TC) and the pile surface roughness. The lower shaft resistance measured in tensile loading is due to the rotation of principal strains that occurs upon reversal of loading direction. Localisation of shear strains occurred within a thin band of sand around the pile shaft.